FROM SANAD TO ALGORITHM: AUTHORITY, RATIONALITY, AND PARTICIPATORY INTERPRETATION OF UṢŪL AL-DĪN IN CYBERSPACE - Taufik Hidayatulloh (Peminat Ilmu Ushuluddin, 2025)
The proliferation of digital media has fundamentally transformed the production, circulation, and legitimation of religious knowledge, including the discipline of uṣūl al-dīn as the foundation of Islamic theology. Traditional structures of authority rooted in scholarly chains of transmission (sanad) and institutional recognition are increasingly mediated by algorithmic visibility, engagement metrics, and participatory interaction within networked digital environments. This study examines how these transformations reshape both the authority and rationality of Islamic theological discourse in cyberspace. Employing a qualitative approach grounded in digital discourse analysis, data were collected through non-participant observation of theological content and interactions on social media platforms, and analyzed using thematic and critical discourse frameworks. The findings reveal a significant epistemic shift from sanad-based legitimacy toward forms of performative and algorithmic authority, where visibility, emotional resonance, and communicative accessibility play central roles. The rationality of kalām, traditionally characterized by systematic and deductive argumentation, has been rearticulated into concise, modular, and visually mediated forms adapted to digital communication structures. Furthermore, theological interpretation emerges as a participatory and dialogical process involving both content creators and audiences, resulting in fluid authority and the distributed production of meaning. Based on these findings, this study proposes the concept of Participatory-Digital Hermeneutics of Uṣūl al-Dīn as a conceptual framework for understanding contemporary theological interpretation. This model highlights four key features: collaborative interpretation, fluid authority, narrative-performative rationality, and networked meaning production. While the normative foundations of ʿaqīdah remain intact, their articulation and public negotiation are increasingly shaped by digitally mediated interaction.